2021
DOI: 10.3390/ijgi10060408
|View full text |Cite
|
Sign up to set email alerts
|

How Image Acquisition Geometry of UAV Campaigns Affects the Derived Products and Their Accuracy in Areas with Complex Geomorphology

Abstract: The detailed and accurate mapping of landscapes and their geomorphological characteristics is a key issue in hazard management. The current study examines whether the image acquisition geometry of unmanned aerial vehicle (UAV) campaigns affects the accuracy of the derived products, i.e., orthophotos, digital surface models (DSMs) and photogrammetric point clouds, while performing a detailed geomorphological mapping of a landslide area. UAV flights were executed and the collected imagery was organized into thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Harwin et al [68] concluded that including oblique images is advised, as they can improve self-calibration of the bundle block adjustment and increase horizontal and vertical accuracy. Similar findings were presented by Kyriou et al [62]; they stated that the combination of nadir and oblique imagery can effectively be used for geomorphological mapping in areas with complex topography and steep slope (>60 • ), to increase the geometric accuracy of UAV data.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Harwin et al [68] concluded that including oblique images is advised, as they can improve self-calibration of the bundle block adjustment and increase horizontal and vertical accuracy. Similar findings were presented by Kyriou et al [62]; they stated that the combination of nadir and oblique imagery can effectively be used for geomorphological mapping in areas with complex topography and steep slope (>60 • ), to increase the geometric accuracy of UAV data.…”
Section: Discussionsupporting
confidence: 82%
“…The image overlaps were 80%. Pictures were taken at 45 • and 90 • angles, as the combination of oblique and nadir images contributes to a more accurate representation of terrain [62]. For planning the UAV mission, we used the DJI GS RTK application.…”
Section: Flight Planning and Acquisition Of Data With Uavmentioning
confidence: 99%
“…This degree of accuracy may be more than sufficient for three-dimensional (3D) modeling projects or environmental monitoring that only requires relative accuracy. But for projects that usually require more accurately geo-referenced outputs, including land surveying, earthwork, topographic surveys, among others, a certain number of GCPs need to be deployed in the survey area [25]- [27]. The absolute or relative coordinates of these GCPs are commonly measured with GNSS RTK [28], [29], total stations [30], [31], among others.…”
Section: Introductionmentioning
confidence: 99%
“…GCPs need to be placed in suitable locations based on the image acquisition geometry to cope with terrain constraints [25], [26]. Following the acquisition of images from UAV surveys, the image coordinates of GCPs in corresponding photos must be obtained to play the role of GCPs in subsequent data processing and analyses, such as aerial triangulation and dense matching [42], [43].…”
Section: Introductionmentioning
confidence: 99%
“…Mass wasting contributes immensely to landscape evolution of a planetary body not only through subaerial modifications, but even through subsurface and underwater modulations (e.g., [3][4][5][6][7][8][9]). In fact, mass movements are one of the most significant geomorphological processes molding the surface of our planet [10][11][12][13]. Interestingly, widely varying mass wasting features have also been identified on other planetary bodies such as the Moon (e.g., [14]), Mercury (e.g., [15]), Venus (e.g., [16]), Mars (e.g., [17][18][19][20][21]), and some outer Solar System satellites (e.g., [22]).…”
Section: Introductionmentioning
confidence: 99%